The effect of estrus detection by progesterone test kits and clinical examination on conception rates in cows - Mustafa Sönmez; Gaffari Türk; Eşref Demirci (Eurasian Journal of Veterinary Sciences)
This study was conducted to compare the effect of estrus detection using progesterone test kits and clinical examination on the conception rate, and to investigate whether the progesterone tests have positive effect on conception rate of cows in field conditions. A total of 136 cows were used in this study. The clinical findings of estrus in cows were examined by visual observation and rectal palpation. Cows were divided into three subgroups considering to the intensity of clinical results. Progesterone levels in serum samples were evaluated using progesterone tesl (Ovulation Test®) kits. Cows were also divided into three subgroups according to the progesteron levels, and then, all cows were artificially inseminated. The conception rates were determined by rectal palpation on 55-60th days following artificial insemination. In this study, the mean overall conception rate was recorded as 65.4%. It has been found that there is no difference (P>0.05) among conception rates of cows which were divided into subgroups by intensity of clinical findings. The conception rates were significantly (P<0.05) higher in cows with low concentrations of progesterone (<1 ng/ml) at insemination lime than those of cows with intermediate concenlrations ol progesterone (12.5 ng/ml) (78.5% vs. 23.8%). In addition, the conception didn't occur in cows with high concentrations ot progesterone (>2,5 ng/ml). In conclusion, the use of practice progesterone tests can be useful lor preventing errors in heat detection and for increasing conception rate in cows which not be detected in estrus by clinical examination.